The Contribution of Arm Muscle Explosive Power and Backward Flexion to the Inward Throw on Football Games - Ishak, Muhammad; Bismar, Ahmad Rum; Sudirman, Sudirman (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This study aims to, among others, (1) determine the contribution of arm muscle explosive power to inward throws in soccer games, (2) determine the contribution of rear strike flex to inward throws in soccer games, (3) determine the contribution of arm muscle explosive power and rear strike flex to inward throws in soccer games. This research belongs to the type of descriptive quantitative research. The population of this study was all FIK UNM students with a sample of 50 people. The data analysis technique used is correlation and regression analysis techniques using the SPSS Version 22 system at a significant level of α0.05. Based on the results of data analysis, this study concluded that: 1) the explosive power of the arm muscles has contributed to the inside throw in the FIK UNM student soccer game by 23%, 2) the rear blow has contributed to the inside throw in the FIK UNM student soccer game by 19.3%, 3) the explosive power of the arm muscles, and the back blow flex has a contribution to the inside throw in the student soccer game FIK UNM is 60.4%.